Langerhans dendritic cell vaccine bearing mRNA-encoded tumor antigens induces antimyeloma immunity after autotransplant - Chung, David J.; Sharma, Sneh; Rangesa, Madhumitha; DeWolf, Susan; Elhanati, Yuval; Perica, Karlo; Young, James W. (Blood advances, 2022)
Posttransplant vaccination targeting residual disease is an immunotherapeutic strategy to improve antigen-specific immune responses and prolong disease-free survival after autologous stem cell transplantation (ASCT) for multiple myeloma (MM). We conducted a phase 1 vaccine trial to determine the safety, toxicity, and immunogenicity of autologous Langerhans-type dendritic cells (LCs) electroporated with CT7, MAGE-A3, and Wilms tumor 1 (WT1) messenger RNA (mRNA), after ASCT for MM. Ten patients received a priming immunization plus 2 boosters at 12, 30, and 90 days, respectively, after ASCT. Vaccines contained 9 × 106 mRNA-electroporated LCs. Ten additional patients did not receive LC vaccines but otherwise underwent identical ASCT and supportive care. At 3 months after ASCT, all patients started lenalidomide maintenance therapy. Vaccinated patients developed mild local delayed-type hypersensitivity reactions after booster vaccines, but no toxicities exceeded grade 1. At 1 and 3 months after vaccines, antigen-specific CD4 and CD8 T cells increased secretion of proinflammatory cytokines (interferon-γ, interleukin-2, and tumor necrosis factor-α) above prevaccine levels, and also upregulated the cytotoxicity marker CD107a. CD4 and CD8 T-cell repertoire analysis showed a trend for increased clonal expansion in the vaccine cohort, which was more pronounced in the CD4 compartment. Although not powered to assess clinical efficacy, treatment responses favored the vaccine arm. Triple antigen–bearing mRNA-electroporated autologous LC vaccination initiated at engraftment after ASCT, in conjunction with standard lenalidomide maintenance therapy for MM, is safe and induces antigen-specific immune reactivity. This trial was registered at www.clinicaltrials.gov as #NCT01995708. •Triple antigen–bearing mRNA-electroporated autologous LC vaccines after ASCT for MM are safe and immunogenic. [Display omitted]